2018
DOI: 10.1111/nin.12249
|View full text |Cite
|
Sign up to set email alerts
|

Once upon a time: Storytelling as a knowledge translation strategy for qualitative researchers

Abstract: Qualitative research should strive for knowledge translation toward the goal of closing the gap between knowledge and practice. However, it is often a challenge in nursing to identify knowledge translation strategies able to illustrate the usefulness of qualitative results in any given context. This article defines storytelling and uses pragmatism to examine storytelling as a strategy to promote the knowledge translation of qualitative results. Pragmatism posits that usefulness is defined by the people affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
1
22
0
3
Order By: Relevance
“…This scientific evidence was shared in diverse settings for narrative engagement, with the aim of gathering "sciencestimulated narratives" across different stakeholders and sectors. The narrative approach used combined insights from different disciplinary ways of narrative working and storying practice (Lewis, 2011;Bourbonnais and Michaud, 2018;Liguori et al, 2021) and participatory methods (McEwen et al, 2016). This way of working recognized that within the United Kingdom, it was challenging to get local people to talk about local drought risk and experience, with the frequent need for researchers to go in more obliquely around wider water behaviors and environment (see Liguori et al, 2021).…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…This scientific evidence was shared in diverse settings for narrative engagement, with the aim of gathering "sciencestimulated narratives" across different stakeholders and sectors. The narrative approach used combined insights from different disciplinary ways of narrative working and storying practice (Lewis, 2011;Bourbonnais and Michaud, 2018;Liguori et al, 2021) and participatory methods (McEwen et al, 2016). This way of working recognized that within the United Kingdom, it was challenging to get local people to talk about local drought risk and experience, with the frequent need for researchers to go in more obliquely around wider water behaviors and environment (see Liguori et al, 2021).…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…The sharing of these powerful stories from inspirational role models may provide a novel approach to effective KT. 62,63 Relational Research Partnership Skills The third approach relates to the relational aspects of research partnerships. Participants' stories revealed that those who engaged in research partnerships were highly motivated and willing to improve their relational research partnership skills (eg, building relationships).…”
Section: Inspirational Role Modelsmentioning
confidence: 99%
“…Narrative enquiry is a way of understanding, organizing and communicating experiences, and in part surrounds the act of storytelling, as the world is 'full of partial stories that run parallel to one another, beginning and ending at odd times' (James, 1907(James, :2010. Within enquiry relating to pragmatism, it can include living via our stories, telling stories of experiences, and modifying stories by retelling and reliving the story (Bourbonnais & Michaud, 2018). Storytelling also entails a dialogical co-construction between people, in which a narrative unfolds yielding possible opportunity (Colapietro, 2013).…”
Section: Through Narrative Enquiry Pragmatists Have Hope That Dialogmentioning
confidence: 99%